KAREKTERISASI OPTIMISASI JARINGAN RANTAI PASOKAN - Nasution, Devi Maiya Sari; Nasution, Palitan; Ahmad Yanie (JMRI Journal of Multidisciplinary Research and Innovation, 2023)
This study proposes a mathematical solution to optimization problems in supply chains. The supply chain analyzed includes suppliers, manufacturers and distribution centers, bearing in mind that orders come from clients to distribution centers. A mathematical model that solves optimization characterization problems regarding the duration and cost of executing client orders is proposed. Many constraints are supported in this mathematical model such as supplier and producer capacity and balanced supply. The aim of the proposed model is to find optimal characteristic solutions that minimize cost and time criteria throughout the entire supply chain process. Mathematical models are tested on supply chains to determine the characteristics of several models that can be used to obtain optimal supply chain networks. This research produces a mathematical model with the function of the procurement model.